Theory-building: working the theory-data spectrum - Engler, Steven Joseph (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2019)
This article illustrates some implications of the view that data, theory and methods should be treated as a matched set. They are inseparable companions, equally essential parts of processes of scholarly research and dissemination. When we focus on one of these dimensions, the others are always implicit. When focus on all of them, our work is more complete, consistent and defensible. This contribution to this special issue highlights the value of focusing more explicitly on the inter-relations between all four levels of scholarly work.